Maxillary sinus floor augmentation through bone densification - Kelly Zaia Barel; Paulo Sérgio Zaidan Maluf (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Objective: Presenting a case of maxillary sinus lifting through alveolar crest by means of bone compacting from bone densification with drills and immediate placement of the dental implant (fixture). Patients who suffer from alveolar bone insufficiency present a common problem in the recovery from osseointegration implants, when a minimum remaining bone extension is necessary for implant stability. On those patients who present great bone loss in the posterior maxilla it is necessary to perform a sinus lifting surgery. The elevation of the sinus floor can be performed in two different ways, as described in the field literature: accessing the lateral window or accessing the maxillary sinus through alveolar crest by means of bone densification, thus allowing oral rehabilitation through dental implants.